Clinical epidemiology and disease burden of adenoviral encephalitis in hospitalized children in China: A nationwide cross‐sectional study - Jiao Tian; Xinyu Wang; Linlin Zhang; Qi Li; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (Wiley, 2023)
ABSTRACT Importance Adenovirus encephalitis is a significant infectious disease of the central nervous system that commonly affects children under the age of 5 and has a profound impact on the health of infants and young children throughout China. National multicenter epidemiological studies have significant public health implications. Objective This study aims to report the epidemiology of adenovirus encephalitis in hospitalized children in China, providing valuable guidance for clinicians. Methods The data utilized in this study were extracted from the comprehensive Futang Update Medical Records database, which comprises discharge medical records collected by 27 tertiary children's hospitals between January 2016 and December 2018 in China. Specifically, the face sheet of discharge medical records encompassed critical sociodemographic variables and basic medical care details. Results In this database, a total of 544 children were hospitalized due to adenoviral encephalitis. The male‐to‐female ratio was 1.62:1, with more boys being affected across different age groups and places of residence. Of the children hospitalized, the highest number of hospitalizations occurred in the 1-3‐year age group and the number of hospitalizations decreased each year from 2016 to 2018. The disease exhibits seasonal characteristics with a pronounced peak in the summer months of June and July. While most children (58%) did not have any significant complications, one‐third of them developed respiratory complications, including pneumonia and acute bronchitis. The median length of stay for adenoviral encephalitis was 7 days, and the median cost of hospitalization was 2145.56 US dollars. Interpretation This study highlights the prevalence of adenovirus encephalitis in hospitalized children in China. Children aged 1-3 years were found to be the main demographic hospitalized due to this condition, with boys being significantly more affected than girls. The seasonal variations of adenovirus encephalitis were also found to be significant. Fortunately, the fatality rate associated with this condition was low, and the prognosis was generally favorable.